Pengaruh Media Gambar Terhadap Minat Belajar Siswa Kelas IV SD Negeri 122365 Pematang Siantar - Indah Nurlelyanna Siringoringo; Andriono Manalu; Selamat Triadil Saragih (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the effect of image media on the learning outcomes of class IV students with sub-theme 2 Diversity of Living Creatures in My Environment at SD Negeri 122365 Pematang Siantar odd semester FY 2023/2024. The type of research in this research is quantitative research. The research population was all students in class IV A of SD Negeri 122365 Pematang Siantar totaling 23 students. The sampling technique in this research issimple random sampling, where the sample selected is a saturated sample. The sample in this study consisted of class IV of state elementary school 122365 Pematang Siantar, totaling 23 students. The results of this study show that the average score is 61.35 and for interest in learning the score is based on an average score of 53.17. The results of the t distribution test at the significance level (ɑ = 0.05), dk = N-1 = 23-1 =22, namely tcount>ttable, then the data has a t distribution with results of 4.046>ttable 2.048 data can be said to have a significant influence. The results of the t-test table prove that there is an influence of image media (X) on interest in learning (Y) with the t-count results. The t-test results are 4.046, while tcount= 2,048. Face tcount> ttablenamely 4.046 > 2.048. . This proves that there is a significant influence from the use of image media on class IV learning interest in subtheme 2 Diversity of Living Creatures in My Environment at SD Negeri 122365 Pematang Siantar.